Islamic Boarding School and Counseling Teachers: The Challenge of Creating Resilient Santri in the New Paradigm - Syarifuddin, Ummah Karimah; Akmal, Mochamad Daffa; Shofiyah, Siti; Chairunnisa, Azzora; Maulitaj Daffa, Tajaufa (Universitas Muhammadiyah Yogyakarta, 2023)
Pesantren has Islamic education management, a unique character, and is able to harmonize with the times. The role of Islamic boarding schools through BK teachers has challenges in the new paradigm of producing tough students since when problems arise, students need a tough personality to deal with them. This study aimed to find out the preparation efforts and the programs owned by Islamic boarding schools in producing tough students in synergy with BK teachers in carrying out their programs. This research method uses descriptive qualitative research through interviews with BK teachers and homeroom teachers at Islamic boarding schools as well as documentation and observation. The results of this study are important for position holders in Islamic boarding schools in preparing tough students through pesantren programs in synergy with the school/madrasah. The study concludes that it is time for policymakers and BK teachers to be literate with the times in the new paradigm era by adjusting the programs of Islamic boarding schools because it cannot be separated from the challenges by providing guidance and counseling services according to the needs of students in terms of making strong individuals.